La consultation publique et la question éthique dans les pratiques d'aménagement urbain paysagé. Éléments théoriques et introduction à l'analyse de cas - Perraton, Charles; Cinq-Mars, Irène (Les Cahiers de droit, 1988)
With ever-growing concern for democracy, space developers and designers have enlisted public consultation onto their roster of communicational strategies. This strategy coincides with the appearance in our societies of a marked trend towards recognizing individual rights. Among the incidences of consultation may be found that of giving meaning to spaces. Thus these tactics and other practices respond to these strategic efforts that are out of phase with users. What kind of relation with people do these new participatory procedures instate which are based on communicational exchanges of a consultative kind ? In questioning users' "power", it is not so much the political, but rather the ethical question that retains our interest here. Specifically, our objective is to produce creteria enabling the appraisal of the "quality" of programming and designing and that of spatial projects. Our viewpoint is extrapolated results from our research in Les pratiques d'espaces libres urbains à Montréal (FCAR EQ-3013).